Economic and social transformation in China challenges and opportunities - Hu, Angang 1953-; Hu, Angang 1953- (Routledge, 2006)
chapter Introduction: How I conducted this China Study -- chapter 1 Why has China's economy grown so fast? -- chapter 2 Comprehensive national power (1980-2000): A comparative study of the US, Russia, Japan, India and China -- chapter 3 Why has China's TFP dropped in 1995-2001? -- chapter 4 From unevenness to coordination for China's regional development (1978-2004) -- chapter 5 China's economic growth and poverty reduction (1978-2002) -- chapter 6 China's macro-economy and health -- chapter 7 Health insecurity: The biggest challenge to human security in China -- chapter 8 Developing human resources to cope with an aging society -- chapter 9 China's urban unemployment and social security (1993-2000) -- chapter 10 Genuine national savings and natural capital cost in China (1970-2001) -- chapter 11 Corruption: an enormous black hole: Public exposure of the economic costs of corruption -- chapter 12 Second transition of the Communist Party of China: From economic development to institution building -- chapter 13 Making policy decision-making more scientific, democratic, systematic and specialized.
Keywords: China; Economic policy; 21st century; China; Social policy; 21st century; Electronic books; China -- Economic policy -- 2000-; China -- Social policy -- 21st century.